2014
DOI: 10.14233/ajchem.2014.16535
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of Aspirin Derivatives

Abstract: Sclerotinia sclerotiorum, Helminthosprium maydis, Botrytis cinerea and Rhizoctonia solani are harmful pathogenic fungi of crops or vegetables 1-4. Over the past decades, synthetic fungicides including carbendazim have been used to prevent them. However, in recent years, they have developed resistance to the fungicides 5-9. Moreover, their scope of resistance continues to expand and has already included many new fungicides 10-12. Therefore, new fungicides are continually required. It is well-known that since as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…1). The chemical identity of the product was confirmed by various spectroscopic techniques consistent with literature reports (Gao et al, 2014;Eissa et al, 2017).…”
Section: Chemical Contextsupporting
confidence: 82%
“…1). The chemical identity of the product was confirmed by various spectroscopic techniques consistent with literature reports (Gao et al, 2014;Eissa et al, 2017).…”
Section: Chemical Contextsupporting
confidence: 82%
“…Mechanistic studies on these reactions revealed that P-centered radicals are involved in these transformations and the mechanism is similar to the one suggested in Scheme 10b. [22][23][24] Scheme 8 6-Arylated phenanthridines via visible-light-induced radical arylation of isonitriles.…”
Section: Radical Isonitrile Insertion Reactions Of 2-isocyanobiphenyl...mentioning
confidence: 99%
“…The Tang and Zhao group reported Mn(OAc) 3 -promoted phosphonyl radical reactions of 2-isocyanobiaryls 367 for the synthesis of 6-phenanthrinephosphonates 368 (Scheme 156) 256. In the presence of radical initiators or oxidants, phosphinic acids as well as phosphinates and their salts can be used for the generation of hydrophosphonyl radicals.…”
mentioning
confidence: 99%